Development of Nickel Hydrosilylation Catalysts. Issue 5 (8th August 2016) - Nakajima, Yumiko; Sato, Kazuhiko; Shimada, Shigeru
Abstract: In this account, our studies on nickel‐catalyzed hydrosilylation reactions are described. A series of (salicylaldiminato)methylnickel complexes efficiently catalyze alkene hydrosilylation under ambient reaction conditions. Commercially available Ni(II) salts, Ni(acac)2 (acac = acetylacetonato) and its derivatives bis(hexafluoroacetylacetonato)nickel(II) and bis (2, 2, 6, 6‐tetramethyl‐3, 5‐heptanedionato)nickel(II), also act as versatile hydrosilylation catalyst precursors in the presence of NaBHEt3 . These systems catalyze the hydrosilylation of various alkenes such as industrially important siloxy‐, amino‐, and epoxy‐substituted ones. The arene‐supported cationic nickel allyl complexes also serve as good catalysts for alkene hydrosilylation at room temperature. These nickel complexes exhibit high selectivity towards the reaction using secondary hydrosilanes. Mechanistic studies based on experiments and DFT calculations support a novel mechanism, which includes a facile Si–H bond cleavage and a Si–C bond formation, assisted by the cooperative action of the allyl ligand. Abstract : There is an increasing demand to develop cheap and earth‐abundant metal hydrosilylation catalysts that can substitute the widely used platinum catalysts. In this account, our studies on nickel‐catalyzed hydrosilylation reactions are summarized. The unique mechanisms that have been proposed based on both experimental and theoretical studies are discussed.